Keyhole Endoscopic-Assisted Transcervical Approach to the Upper and Middle Retrostyloid Parapharyngeal Space: An Anatomic Feasibility Study - Eguiluz-Melendez, Aldo; Torres-Bayona, Sergio; Vega, María Belen; Hernández-Hernández, Vanessa; Wang, Erik W.; Snyderman, Carl H.; Gardner, Paul A. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objectives The aim of this study was to describe the anatomical nuances, feasibility, limitations, and surgical exposure of the parapharyngeal space (PPS) through a novel minimally invasive keyhole endoscopic-assisted transcervical approach (MIKET).Design Descriptive cadaveric study.Setting Microscopic and endoscopic high-quality images were taken comparing the MIKET approach with a conventional combined transmastoid infralabyrinthine transcervical approach.Participants Five colored latex-injected specimens (10 sides).Main Outcome Measures Qualitative anatomical descriptions in four surgical stages; quantitative and semiquantitative evaluation of relevant landmarks.Results A 5 cm long inverted hockey stick incision was designed to access a corridor posterior to the parotid gland after independent mobilization of nuchal and cervical muscles to expose the retrostyloid PPS. The digastric branch of the facial nerve, which runs 16.5 mm over the anteromedial part of the posterior belly of the digastric muscle before piercing the parotid fascia, was used as a landmark to identify the main trunk of the facial nerve. MIKET corridor was superior to the crossing of the accessory nerve over the internal jugular vein within 17.3 mm from the jugular process. Further exposure of the occipital condyle, vertebral artery, and the jugular bulb was achieved.Conclusion The novel MIKET approach provides in the cadaver straightforward access to the upper and middle retrostyloid PPS through a natural corridor without injuring important neurovascular structures. Our work sets the anatomical nuances and limitations that should guide future clinical studies to prove its efficacy and safety either as a stand-alone procedure or as an adjunct to other approaches, such as the endonasal endoscopic approach.
Keywords: minimally invasive; endoscopic-assisted; transcervical approach; keyhole approach; retrostyloid parapharyngeal space